Pengaruh Gaya Kepemimpinan terhadap Produktivitas Kerja Pegawai BAZNAS Kabupaten Sukabumi - Alfiana, Muhammad Marse; Rustandi, Ridwan; Sanusi, Irfan (Tadbir: Jurnal Manajemen Dakwah, 2024)
In this competitive globalization era, improving work quality and employee productivity is an important challenge for organizations in various sectors. Leadership style is known to be a key factor influencing this productivity. The main objective of this study is to investigate how much and what influence leadership style has on the work productivity of BAZNAS Sukabumi district employees. This research method uses a survey with a questionnaire as a data collection tool from 27 Sukabumi Regency BAZNAS employees. The research findings confirm the positive and significant influence of the leadership style possessed by the leader on employee work productivity. The results show that the leadership style variable is able to explain 28% of the variation in employee work productivity, emphasizing the important role of leadership style in increasing organizational efficiency and performance. This study also details that a leadership style that is smart, understands people, and has good management skills has a significant positive impact on employee self-development, morale, and improvement of work quality and efficiency.